2008
DOI: 10.1074/jbc.m803116200
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction between the Human T Cell Leukemia Virus Type 1 Basic Leucine Zipper Factor (HBZ) and the KIX Domain of p300/CBP Contributes to the Down-regulation of Tax-dependent Viral Transcription by HBZ

Abstract: Activation of human T cell leukemia virus type 1 (HTLV-1) transcription is established through the formation of protein complexes on the viral promoter that are essentially composed of the cellular basic leucine zipper (bZIP) transcription factor cAMP-response element-binding protein (CREB (or certain other members of the ATF/CREB family), the HTLV-1-encoded transactivator Tax, and the pleiotropic cellular coactivators p300/CBP. HTLV-1 bZIP factor (HBZ) is a protein encoded by HTLV-1 that contains a bZIP domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
194
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(208 citation statements)
references
References 67 publications
11
194
0
3
Order By: Relevance
“…HBZ is a potent suppressor of Tax-mediated virus-gene transcription by interacting with activating transcription factor/cAMP responsive element-binding protein (CREB) and CREB-binding protien/p300 on the 5Ј-LTR promoter. 24,34,35 The HBZ role in the tightly regulated pattern of HTLV-1-gene expression also is suggested by HBZ repression of Gag-p19 synthesis in stable virus-producing cell clones. 36 Kinetic study of gene expressions in cells transiently transfected with the HTLV-1-provirus plasmid and in newly infected PBMCs showed that Gag/Pol, Tax/Rex, and Env mRNA are detected first and at their highest levels, whereas HBZ transcription was significantly lower and peaked later.…”
Section: Discussionmentioning
confidence: 99%
“…HBZ is a potent suppressor of Tax-mediated virus-gene transcription by interacting with activating transcription factor/cAMP responsive element-binding protein (CREB) and CREB-binding protien/p300 on the 5Ј-LTR promoter. 24,34,35 The HBZ role in the tightly regulated pattern of HTLV-1-gene expression also is suggested by HBZ repression of Gag-p19 synthesis in stable virus-producing cell clones. 36 Kinetic study of gene expressions in cells transiently transfected with the HTLV-1-provirus plasmid and in newly infected PBMCs showed that Gag/Pol, Tax/Rex, and Env mRNA are detected first and at their highest levels, whereas HBZ transcription was significantly lower and peaked later.…”
Section: Discussionmentioning
confidence: 99%
“…The recently identified HBZ (HTLV-1 bZIP) factor acts as a negative regulator of TAX-mediated viral transactivation by heterodimerising with CREB, CREB2 and p300/CBP (Clerc et al, 2008). HBZ also modulates AP1 pathway by interacting with c-Jun, JunB and JunD.…”
Section: Hbzmentioning
confidence: 99%
“…Alors que HBZ est incapable de s'homodimériser, il peut former in vivo des dimères avec des membres de la famille ATF/CREB et Jun (Figure 2) [9,[17][18][19][20][21]. En outre, grâce à son domaine d'activation, HBZ interagit aussi avec les cofacteurs transcriptionnels CBP/p300 [22]. Il est frappant de constater que HBZ cible les facteurs nucléaires qui sont impliqués dans le contrôle de la transcription virale Tax-dépendante (Figure 1).…”
Section: Hbz Déjoue Le Contrôle Immunitaireunclassified
“…Il est frappant de constater que HBZ cible les facteurs nucléaires qui sont impliqués dans le contrôle de la transcription virale Tax-dépendante (Figure 1). En fait, nous avons pu démontrer que HBZ régule négativement la transcription des autres gènes viraux en inhibant l'association de Tax avec CREB sur le promoteur du LTR 5' et en empêchant le recrutement de CBP/p300 sur ce même promoteur (Figure 3) [21,22]. …”
Section: Hbz Déjoue Le Contrôle Immunitaireunclassified
See 1 more Smart Citation